(untitled) (Vallis Aurea, 2024)
Combating domestic violence requires an interdisciplinary approach to solving this serious social problem, with law, legal practice and science playing a very important role. Theoretically, it appears as physical, psychological, sexual and economic violence, while the victims are mostly weaker social groups - women, children and the elderly. Numerous international documents, as well as national regulations in the field of family, criminal and misdemeanor law, provide protection against domestic violence, but statistical indicators do not speak in favor of sufficient effectiveness in their application in practice. The COVID-19 pandemic has in a way further intensified the existing ones, but also created new challenges in the fight against domestic violence. Measures of social isolation, unavailability of competent institutions and general uncertainty are just some of the causes that have contributed to the increase in the number of cases of domestic violence, and the possibility of protecting victims of such treatment.